2010
DOI: 10.1080/10400430903519944
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Perspectives on the Accessibility of E-Learning in Canadian Colleges and Universities

Abstract: An exploratory study identified and compared the views of 77 campus disability service providers, 38 professors, and 45 e-learning professionals from Canadian colleges and universities regarding their experiences with e-learning and its accessibility to students with disabilities. Findings indicate that all groups saw benefit in having someone who makes e-learning accessible to students with disabilities on campus and that problems related to e-learning accessibility were most likely to go to campus disability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 3 publications
0
12
0
Order By: Relevance
“…One key advantage of digital mindfulness-based interventions (d-MBIs) is their accessibility. d-MBIs can reduce geographical, logistical, and financial constraints that would otherwise prevent access to training (Asuncion et al, 2010). d-MBIs can also be effectively standardized.…”
Section: How Can Evidence-based Mindfulness Training Be Made Availablmentioning
confidence: 99%
“…One key advantage of digital mindfulness-based interventions (d-MBIs) is their accessibility. d-MBIs can reduce geographical, logistical, and financial constraints that would otherwise prevent access to training (Asuncion et al, 2010). d-MBIs can also be effectively standardized.…”
Section: How Can Evidence-based Mindfulness Training Be Made Availablmentioning
confidence: 99%
“…The message from the federal government about technology accessibility is over a decade and a half old and has been communicated in statutes, regulations, and policy. Unfortunately, however, technology accessibility, as an innovation, has not yet fully diffused in K–12, as evidenced by (1) the plethora of inaccessible technologies present in K–12 classrooms (Asuncion et al, 2010; Bray et al, 2003; Fajardo-Flores et al, 2007; Fichten et al, 2009; Kamei-Hannan, 2008; Phipps & Kelly, 2013; Schaffhauser, 2013) and (2) the grave concerns expressed by disability rights organizations about inaccessible instructional technologies used in K–12 classrooms (National Federation of the Blind, 2015; Nightingale v. Seattle School District , 2014; Riccobono et al, 2015; Riccobono & Rosenblum, 2016).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Discussions of inaccessible instructional technologies in the literature have focused on Internet-based technologies, which are common in both e-learning and traditional face-to-face learning environments. Examples of inaccessible technologies that can be found in K–12 classrooms and are likely to pose barriers for students with disabilities include learning/content management systems (Fajardo-Flores et al, 2007), school websites (Bray, Flowers, & Gibson, 2003; Bray, Flowers, Smith, & Algozzine, 2003; Krach & Jelenic, 2009; Opitz, Savenye, & Rowland, 2003), computer-adapted testing (Kamei-Hannan, 2008), and other e-learning resources (Asuncion et al, 2010; Fichten et al, 2009; Phipps & Kelly, 2013). Studies examining the accessibility of K–12 websites found that 74.3% of 120 school district websites contained accessibility barriers (Bray, Flowers, & Gibson, 2003) and 57.4% of 244 elementary school websites contained accessibility barriers (Bray, Flowers, Smith, et al, 2003).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Alongside the argument that stakeholders should have shared or distributed expertise is the claim that that there has been a tendency for some stakeholders to rely on others to take responsibility for leading change in accessibility and digital inclusion practices. For example, in a survey of disability service providers faculty and elearning professionals in Canada, Asuncion et al (2010) found that campus disability service providers were most likely to believe that problems related to the accessibility of e-learning were their responsibility and e-learning professionals were least likely to claim responsibility. Observing UK practice, JISC (2006) and Mariger (2011) both 7 noted that there had been a tendency to rely on disability officers and support services to take the main responsibility for accessibility.…”
mentioning
confidence: 99%